Concentration Effect of Gd3+ on the Structural, Optical and Spectroscopic Properties of NdVO4 Nanoparticles. Issue 205 (12th February 2020) - Raina, Bindu; Verma, Seema; Thakur, Sonali; Ahmad, Yaseen; Bamzai, K. K.
Abstract: Neodymium vanadate with concentration of gadolinium as 3% and 5% having general formulae Gdx Nd1-x VO4 where x = 0.03 and 0.05 was prepared by chemical route technique. The effect of concentration of gadolinium on the structural, optical and spectroscopic properties was explained by various characterization techniques. Powder X-ray diffraction study suggests tetragonal zircon structure; various parameters such as crystallite size, volume and X-ray density were calculated. A change in morphology with the change in concentration of gadolinium was observed through scanning electron microscopy. Ultraviolet absorption spectroscopy shows various transitions from ground state to various excited state within 4f shell, and variation in the optical band gap calculated by Tauc plot is due to the incorporation of Gd 3+ ions.